2014
DOI: 10.4161/psb.28973
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonoyl-l-isoleucine hydrolase 1 (JIH1) contributes to a termination of jasmonate signaling inN. attenuata

Abstract: In the world of complex ecological interactions, optimal performance requires maintenance of homeostasis. For instance, in response to herbivore attack, plants reconfigure their metabolism and produce potent defensive secondary metabolites 1-3 ; a process mediated by the highly conserved jasmonate signaling pathway. [4][5][6][7] The jasmonate signaling cascade is induced in response to herbivore attack and leads to the rapid accumulation of jasmonic acid (JA) and its bioactive form -jasmonoyl-LIle (JA-Ile) -wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…“Dunnart” could have therefore, had a lower abundance due to an earlier mobilisation of the pathogen-triggered signals and subsequent conversion and deactivation of the bioactive jasmonoyl-isoleucine into a non-active conjugate when it was no longer needed. These signalling hormones cause transcriptomic and metabolic reconfigurations that aid in plant defence responses [ 61 , 62 ]. Many different jasmonate precursors and derivatives have been known to exhibit biological activity, including jasmonic-amino acid conjugates [ 63 ], of which two were identified in this study in response to Ps-c infection.…”
Section: Discussionmentioning
confidence: 99%
“…“Dunnart” could have therefore, had a lower abundance due to an earlier mobilisation of the pathogen-triggered signals and subsequent conversion and deactivation of the bioactive jasmonoyl-isoleucine into a non-active conjugate when it was no longer needed. These signalling hormones cause transcriptomic and metabolic reconfigurations that aid in plant defence responses [ 61 , 62 ]. Many different jasmonate precursors and derivatives have been known to exhibit biological activity, including jasmonic-amino acid conjugates [ 63 ], of which two were identified in this study in response to Ps-c infection.…”
Section: Discussionmentioning
confidence: 99%
“…The level of plant defense induction is regulated by both the biosynthesis and degradation of JA-Ile (Figure 1). Whereas the JAR1 protein conjugates jasmonate and isoleucine to form JA-Ile (Koo & Howe, 2009;Staswick et al, 2002), experiments with Nicotiana attenuata showed that JA-Ile can be inactivated by JIH1-mediated cleavage to jasmonate and isoleucine (Woldemariam et al, 2012(Woldemariam et al, , 2014. Similarly, Arabidopsis thaliana (Arabidopsis) iar3 ill6 double knockouts, which are defective in JA-Ile deconjugation, exhibited increased JA-Ile accumulation (Marquis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The level of plant defense induction is regulated by both the biosynthesis and degradation of JA-Ile (Figure 1). Whereas the JAR1 protein conjugates jasmonate and isoleucine to form JA-Ile (Staswick et al, 2002; Koo and Howe, 2009), experiments with Nicotiana attenuata showed that JA-Ile can be inactivated by JIH1-mediated cleavage to jasmonate and isoleucine (Woldemariam et al, 2012; Woldemariam et al, 2014). Similarly, Arabidopsis thaliana (Arabidopsis) iar3 ill6 double knockouts, which are defective in JA-Ile deconjugation, exhibited increased JA-Ile accumulation (Marquis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%